Montelukast in hospitalized patients diagnosed with COVID-19. (7th April 2022) - Khan, Ahsan R.; Misdary, Christian; Yegya-Raman, Nikhil; Kim, Sinae; Narayanan, Navaneeth; Siddiqui, Sheraz; Salgame, Padmini; Radbel, Jared; Groote, Frank De; Michel, Carl; Mehnert, Janice; Hernandez, Caleb; et al.
Abstract: Objective: Several therapeutic agents have been assessed for the treatment of COVID-19, but few approaches have been proven efficacious. Because leukotriene receptor antagonists, such as montelukast have been shown to reduce both cytokine release and lung inflammation in preclinical models of viral influenza and acute respiratory distress syndrome, we hypothesized that therapy with montelukast could be used to treat COVID-19. The objective of this study was to determine if montelukast treatment would reduce the rate of clinical deterioration as measured by the COVID-19 Ordinal Scale. Methods: We performed a retrospective analysis of COVID-19 confirmed hospitalized patients treated with or without montelukast. We used "clinical deterioration" as the primary endpoint, a binary outcome defined as any increase in the Ordinal Scale value from Day 1 to Day 3 of the hospital stay, as these data were uniformly available for all admitted patients before hospital discharge. Rates of clinical deterioration between the montelukast and non-montelukast groups were compared using the Fisher's exact test. Univariate logistic regression was also used to assess the association between montelukast use and clinical deterioration. A total of 92 patients were analyzed, 30 who received montelukast at the discretion of the treating physician and 62 patients who did not receive montelukast. Results: Patients receiving montelukast experienced significantly fewer events of clinical deterioration compared with patients not receiving montelukast (10% vs 32%, p = 0.022). Our findings suggest that montelukast associates with a reduction in clinical deterioration for COVID-19 confirmed patients as measured on the COVID-19 Ordinal Scale. Conclusions: Hospitalized COVID-19 patients treated with montelukast had fewer events of clinical deterioration, indicating that this treatment may have clinical activity. While this retrospective study highlights a potential pathway for COVID-19 treatment, this hypothesis requires further study by prospective studies.